(3GdEYdGe HSf GdgLQI Edi GdTGes - (3GdHbGYj , EHQGgje Hf YeQ Hf MSf GdQHGW Hf Ydj Hf CHj HcQ GdHbGYj GdTGaYj, HQgGf GdOjf CHh GdMSf,J (B885 (3g` s
(3ChdgG (B:s
(3hHYO agPG cJGH cfJ Cf GdfHi Udi Gddg Ydjg hYdi Bdg hSde bGd deG ef Ydi CNJ YOi Hf MGJe QVi Gddg YfgeG s
(3BNQgG (B:s
(3df JHQM gPg GdCeI efUhQjf GjfeG JhLghG dGjVQge ef NPdge ef GdfGS MJi jCJi GeQ Gddg GcKQge Cgd GdTGe s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B71s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B143 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B22 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs